Pengaruh Brand Personality dan Produk Quality Terhadap Brand Love dan Brand Brand Loyality pada Depo Bangunan Sidoarjo - Athoillah; Nuraeni; Sulhan, S.Sos. (CV. Satria Jaya, 2024)
The purpose of this study was to determine the effect of brand personality, product quality, and brand love in building brand loyalty in consumers of Sidoarjo building depot. The sampling technique used in this study is non-probability sampling using purposive sampling and the research sample was 117 respondents, in this study the consumer depo building of Sidoarjo. The type of data and this study are primary data using quantitative research methods and analysis The data in this study used path analysis with the help of SPSS version 22. The results in this study indicate that: (1) brand personality has a significant effect on brand love in the consumer depo building in Sidoarjo (2) product quality has a significant effect on brand love in the customer depo building in Sidoarjo (3) brand personality has a significant effect on brand loyalty in consumers Sidoarjo building depot (4) quality products do not have a significant effect on brand loyalty to consumers of Sidoarjo building depot and (5) brand love has a significant effect on brand loyalty on consumers of Sidoarjo building depo